Complicaciones más frecuentes durante la obturación de los conductos radiculares. Revisión Bibliográfica - Iñiguez Pineda, Katherine Michelle (2022)
Endodontics is the part of dentistry in charge of the study of the etiology, diagnosis, prevention and treatment of diseases of the pulp, periapical tissues, as well as accidents and complications that may occur during the course of treatment, the success or failure of endodontic therapy is evaluated by clinical signs and symptoms, as well as radiographic findings of the treated tooth. Through the present work, a study of the main complications that occur during the obturation of root canals was carried out, as well as the corresponding solution for each complication, taking into account the clinical considerations for its prevention. A bibliographic review was carried out, due to the fact that in order to carry it out it was necessary the previous compilation of information from different media, PubMed, Redalyc, Latindex, Repositories, Medigraphic, Elseiver, InfoMed, Scielo, etc. The bibliography was analyzed in order to identify the most frequent complications that cause during obturation and to describe the parameters that lead to the presence of these accidents. The information was analyzed and synthesized obtaining as conclusions that the most frequent complications that occur after obturation are: Overobturation, overextension, underobturation and underextension, in addition it was possible to verify some complications that occur during this process such as vertical fracture in root canals and fracture of the obturation instruments and in the same way it was possible to identify their possible corresponding solutions for each one of them